The environmental movement : then and now - Stefoff, Rebecca, 1951- (America: 50 years of change., 2018)
Examines the history of the environmental movement from its inception in the early 1960s with the publication of Rachel Carson's book "Silent Spring" through the modern shift in utilizing wind and solar power and the signing of the Paris Climate Accord in 2015. Includes a timeline, text-related questions, a glossary, resources for further information, and color photographs.